Optimization of self-nanoemulsifying formulations for weakly basic lipophilic drugs: role of acidification and experimental design - Ahmad Abdul-Wahhab Shahba; Kazi Mohsin; Fars Kaed Alanazi; Sayed Ibrahim Abdel-Rahman
ABSTRACT Formulators face great challenges in adopting systematic approaches for designing self-nanoemulsifying formulations (SNEFs) for different drug categories. In this study, we aimed to build-up an advanced SNEF development framework for weakly basic lipophilic drugs, such as cinnarizine (CN). First, the influence of formulation acidification on CN solubility was investigated. Second, formulation self-emulsification in media with different pH was assessed. Experimentally designed phase diagrams were also utilized for advanced optimization of CN-SNEF. Finally, the optimized formulation was examined using cross polarizing light microscopy for the presence of liquid crystals. CN solubility was significantly enhanced upon external and internal acidification. Among the various fatty acids, oleic acid-based formulations showed superior self-emulsification in all the tested media. Surprisingly, formulation turbidity and droplet size significantly decreased upon equilibration with CN. The design was validated using oleic acid/Imwitor308/Cremophor El (25/25/50), which showed excellent self-nanoemulsification, 43-nm droplet size (for CN-equilibrated formulations), and 88 mg/g CN solubility. In contrast to CN-free formulations, CN-loaded SNEF presented lamellar liquid crystals upon 50% aqueous dilution. These findings confirmed that CN-SNEF efficiency was greatly enhanced upon drug incorporation. The adopted strategy offers fast and accurate development of SNEFs and could be extrapolated for other weakly basic lipophilic drugs.